The Influence Money Flows on Movement of Stock Prices in Indonesia: An Analysis on Banking Industry - Rozak, Abdul; Rinta Suhardi, Agatha; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The effect of interest rates and money supply on the movement of stock prices has become a major topic of discussion with the goal of analyzing two variables toward stock price volatility at banking companies listed on the Indonesia Stock Exchange for the 2011-2015 period. The method used is explanatory research with descriptive and verification. Empirically, the results showed that there is a very strong relation between interest rates and money supply, amounted to 0.809, with a high impact on stock prices in the banking sector, amounted to 64.3%. The t-test results showed that when the value of the interest rate increases by 1 unit, assuming other variables are fixed, it will increase the stock price by 1,252. Then, if the value of money supply increased by 1 unit, assuming other variables are fixed, it would increase the price of shares to 47.737. While the results of the ANOVA test with a significance level of 0.000 obtained a calculated F-value of 42.135 > F-table at 3.16. Thus, jointly, variable interest rates and money supply significantly influence the price of state-owned banking sector stocks.